How to do everything to fight spam, viruses, pop-ups & spyware - Feinstein, Ken. (New York : McGraw Hill Education, 2004)
Swat spam, vanquish viruses, knock down pop-ups, and expose spyware with help from this one-of-a-kind resource. Loaded with insightful advice, practical tips, and trial software, this book-and-CD defense will help you rid your computer of the perils and nuisances of Web surfing once and for all. Author and tech expert Ken Feinstein gives easy-to-understand explanations of the technologies at work, and just exactly what steps you can take to take back your e-mail, your surfing enjoyment, your privacy, and your computer. Love surfing the Web but are aggravated by the onslaught of pop-up ads, Spam, and unwelcome spyware and adware programs living on your hard drive? This work shows you how to rid your computer of these nuisances, to streamline your web surfing experience, protect your privacy, and improve your overall computer experience.
PART I: Fight SpamChapter: 1 Avoid SpamChapter: 2 Using Spam-Filtering SoftwareChapter: 3 Advanced Spam-Fighting TechniquesPART II: Fight VirusesChapter: 4 Avoid VirusesChapter: 5 Use Antivirus SoftwareChapter: 6 Treat a Virus InfectionPART III: Fighting Spyware and Adware Chapter: 7 Avoid Spyware and Adware Chapter: 8 Use Spyware-Removal Utilities and Firewalls Chapter: 9 Remove SpywarePART IV: Fight Pop-Ups Chapter: 10 Avoid Pop-Ups Chapter: 11 Use Pop-Up Blocking SoftwarePART V: AppendixesAppendix: A Windows XP Service Pack 2Appendix: B What's on the CD
Includes index.
Keywords: SPAM (ELECTRONIC MAIL)